Virus and microbial loop dynamics over an annual cycle in three contrasting Antarctic lakes - Madan, NJ; Marshall, WA; Laybourn-Parry, J (Freshwater Biology, 2005)
1. Viral and microbial loop dynamics were investigated over an annual cycle in threecontrasting saline Antarctic lakes Highway Lake (salinity 4&), Pendant Lake (salinity19&) and Ace Lake, a meromictic system (with a mixolimnion salinity of 18&) in order toassess the importance of viruses in extreme, microbially dominated systems.2. Virus like particles (VLP) showed no clear seasonal pattern, with high concentrationsoccurring in both winter and summer (range 0.89 107 0.038 to12.017 107 1.28 mL)1). VLP abundances reflected lake productivity based on chlorophylla concentrations. Bacterial abundances and biomass did not correlate with VLPnumbers except in Pendant Lake, the most productive of the three lakes studied.3. Pendant Lake supported the highest bacterial biomass (range Highway: 18.44 1.35 to59.43 2.80 ng C mL)1; Ace: 14.42 2.69 to 68.39 2.95 ng C mL)1; Pendant: 31.36 3.94to 115.95 4.49 ng C mL)1) so that virus to bacteria ratios (VBR) (range 30.48 7.96 to96.67 8.21) were higher in Ace Lake (range 30.58 3.98 to 80.037 1.60) and HighwayLake (range 18.63 3.12 to 126.74 6.50).4. Negative correlations occurred between VLP and cryptophytes (dominant phototrophicnanoflagellates), suggesting that they were not hosts to lytic viruses. Among the otherprotists only the heterotrophic nanoflagellates of Highway Lake (dominated by the marinechoanoflagellate Diaphanoeca grandis) showed a positive correlation with VLP.5. The VLP was negatively correlated with photosynthetically active radiation (PAR) andtemperature, both of which increased with ice thinning and breakout, increasing viraldecay. In winter VLP probably persisted in cold, dark water.6. High VLP concentrations and high VBR (values at the upper end of those reported formarine and lacustrine systems) indicated that viruses, most of which were probablybacteriophage, are a major element within the microbial communities in extreme, salinelakes.